Root Diseases of Shisham (Dalbergia sissoo Roxb.) - Bakshi, B. K.; Arora, K. K.; Singh, Sujan (Indian Forester, 1957)
A significant correlation has been observed between the soil texture and the incidence of root diseases in shisham. In sand or loamy sand soils, shisham grows healthy. Root diseases which begin to manifest on shisham growing in sandy loam soils, increase to high proportion in clay loam or clay soils. In plantations of the species, soil texture should determine whether the site is suitable for shisham. No such correlation has however been found between pH of soils and disease incidence in shisham.